EKSTRAKSI PEKTIN DARI KULIT BUAH PISANG KEPOK (Musa paradisiaca) - Farida Hanum, Martha Angelina Tarigan, Irza Menka Deviliany Kaban (Universitas Sumatera Utara, 2012)
Pectin are polymer of D-galacturonic acid connected by β-1,4 glucosidic. Pectin are widely used in pharmaceutical, food and beverage industries. This research was expected to took advantage of banana peels (Musa paradisiaca) by producing pectin. The research used an extraction method by using acid solvent in additional to ethanol to form the sediment of pectin and the last step is drying in order to get dry pectin. The fixed variables which were used in this research were 10 grams banana peels, 10% water content of sample, and chloride acid solvent. Extraction process was carried out by pH 1; 1,5; 2; extraction time of 70, 80, 90, 100 minute, and temperature of 80 oC, 90 oC. The results showed that the highest yield of pectin extraction was obtained at temperature of 80 oC, pH 1,5 during 80 minute with 11,88% water content, 0,98% ash content, and 3,72% the methoxyl content.Keywords : extraction, drying, pectin, yield, methoxyl content